FACTORS AFFECTING STUDENT LEARNING ACHIEVEMENT IN ECONOMICS SUBJECTS: FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Bunga Bunga; Dicky Iranto; Sri Indah Nikensari (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
This research was conducted to determine how much influence learning interest, effectiveness of learning media, and learning motivation have on learning achievement in class X economics at SMA Negeri 105 Jakarta during distance learning (PJJ) with learning motivation as an intervening variable. The method used is a quantitative method with a causal approach to causality. The population in this study were students of class X IPS SMA Negeri 105 Jakarta, amounting to 117 students. Determination of the sample using a saturated sample technique by making members of the population as a sample in the study. The data collection technique in this study used a survey method with a closed questionnaire via Google Form. The data used in this study are primary data for the independent variable (X) and secondary data for the dependent variable (Y). The results of this study indicate that the positive and significant relationship is directly and indirectly between the independent variable on the dependent variable